Occurrence of graft‐versus‐host disease increases mortality after umbilical cord blood transplantation for acute myeloid leukaemia: a report from Eurocord and the ALWP of the EBMT. (6th November 2017) - Baron, F.; Ruggeri, A.; Beohou, E.; Labopin, M.; Mohty, M.; Sanz, J.; Vigouroux, S.; Furst, S.; Bosi, A.; Chevallier, P.; Cornelissen, J. J.; Michallet, M.; et al.
Abstract: Background: The efficacy of umbilical cord blood transplantation (UCBT) as treatment for acute myeloid leukaemia (AML) relies on immune‐mediated graft‐versus‐leukaemia effects. Previous studies have suggested a strong association between graft‐versus‐host disease (GVHD) occurrence and graft‐versus‐leukaemia effects after allogeneic hematopoietic cell transplantation. Methods: Here, we evaluated the kinetics of relapse rate in correlation with GVHD occurrence after UCBT. The kinetics of relapse rate over time in correlation to GVHD occurrence were assessed by calculating the relapse rate per patient‐year within sequential 90‐day intervals. The impact of GVHD on relapse and mortality was further studied in multivariate Cox models handling GVHD as a time‐dependent covariate. Results: The study included data from 1068 patients given single ( n  = 567) or double ( n  = 501) UCBT. The proportion of patients with grade II, III and IV acute GVHD was 20%, 7% and 4%, respectively. At 2 years, the cumulative incidence of chronic GVHD was 42%, the cumulative incidence of relapse was 32%, and overall survival was 32% as well. Relapse rates declined gradually over time during the first 30 months after transplantation. There was a possible suggestion that grade II–IV acute (HR = 0.8, P  = 0.1) and chronic (HR = 0.65, P  = 0.1) GVHD decreased relapse risk. However, grade II–IV acute GVHD significantly increased early (the first 18 months after UCBT) mortality (HR = 1.3, P  = 0.02), whilst chronic GVHD increased each early (HR = 2.7, P  < 0.001) and late (HR = 4.9, P  < 0.001) mortality after UCBT. Conclusions: The occurrence of grade II–IV acute or chronic GVHD each increases overall mortality after UCBT for AML mitigating the possible graft‐versus‐leukemia effect of GVHD.